An integrated approach for design and construction of drawbells in Block Cave Mines - Bustos Salgado, Nadia (Curtin University, 2022)
Drawbell connects the production and undercutting levels in block cave mines. The variables controlling a successful drawbell construction include; rock mass strength, blast damage and induced stress redistribution. Historically these variables have been analyzed separately. This thesis presents a new approach to integrate all the variables contributing to performance in a framework called Integrated Geotechnical Data (IGD). The IGD allows a quantitative analysis to improve both design and construction of a drawbell